Structural protein alterations to resistance and endurance cycling exercise training - Parcell, A. C.; Woolstenhulme, M. T.; Sawyer, R. D. (The Journal of Strength and Conditioning Research, 2009)
The muscle cytoskeleton is necessary for the effective transmission of forces generated by actin-myosin interactions. We have examined the impact of muscle force and exercise volume on the cytoskeleton by measuring desmin and dystrophin content in human skeletal muscle after 12 weeks of progressive resistance or endurance cycle training. Muscle biopsies of the vastus lateralis were obtained before and after training. Desmin and dystrophin content was determined using immunoblotting techniques. After resistance training, desmin content increased 82 ± 18% (p < 0.05), whereas there was no change in desmin content with endurance cycling. Dystrophin content did not change in either group. One-repetition maximum and Vo2max increased (p < 0.05) in the resistance and endurance groups, respectively. These data demonstrate that a high-tension stimulus impacts the cytoskeleton in contrast to high-volume concentric contractions. The tensile loading and eccentric components of resistance training are implicated in desmin alterations. Indeed, the functional improvements resulting from resistance training may be related in part to the mechanical integration provided by the desmin protein.